The stay of proceedings as a remedy in criminal cases: abusing the abuse of process concept. - Paciocco, David M. (Criminal Law Journal, 1991)
Basis for the jurisdiction to stay proceedings - comparison of Commonwealth countries - rationale for the jurisdiction to stay proceedings - relationship between jurisdiction and remedy.